Quality-Based Backlight Optimization for Video Playback on Handheld Devices. (4th July 2007) - Cheng, Liang; Mohapatra, Shivajit; El Zarki, Magda; Dutt, Nikil; Venkatasubramanian, Nalini
Abstract : For a typical handheld device, the backlight accounts for a significant percentage of the total energy consumption (e.g., around 30% for a Compaq iPAQ 3650). Substantial energy savings can be achieved by dynamically adapting backlight intensity levels on such low-power portable devices. In this paper, we analyze the characteristics of video streaming services and propose a cross-layer optimization scheme called quality adapted backlight scaling (QABS) to achieve backlight energy savings for video playback applications on handheld devices. Specifically, we present a fast algorithm to optimize backlight dimming while keeping the degradation in image quality to a minimum so that the overall service quality is close to a specified threshold. Additionally, we propose two effective techniques to prevent frequent backlight switching, which negatively affects user perception of video. Our initial experimental results indicate that the energy used for backlight is significantly reduced, while the desired quality is satisfied. The proposed algorithms can be realized in real time.